Acetazolamide lowers intracranial pressure and modulates the cerebrospinal fluid secretion pathway in healthy rats. (3rd April 2017) - Uldall, Maria; Botfield, Hannah; Jansen-Olesen, Inger; Sinclair, Alexandra; Jensen, Rigmor
Highlights: Acetazolamide lowers intracranial pressure in healthy rats. Acetazolamide inhibits the activity of the Na/K ATPase. Acetazolamide increase aquaporin 1 in the membrane of choroid plexus. Acetazolamide has a dual action in choroid plexus affecting both ion transport and protein expression. Abstract: Acetazolamide is one of the most widely used drugs for lowering intracranial pressure (ICP) and is believed to reduce cerebrospinal fluid (CSF) secretion via its action on the choroid plexus (CP). In the CP the main driving force for CSF secretion is primarily active transport of Na + ions facilitated by the Na/K ATPase. Transmembrane water channels, known as aquaporins (AQP), are also present in the CP and play an important role in the movement of water. In the present study, we investigated the effect of a single dose acetazolamide on the activity of the Na/K ATPase and ICP. Furthermore, we investigated the expression of Na/K ATPase, AQP1 and AQP4 in the CP tissue following acetazolamide treatment. 12 female Sprague Dawley rats were randomized into two groups; one group received 200 mg acetazolamide and the other vehicle treatment. All animals were subjected to ICP recordings and the CP tissue was collected for qPCR and western blot analysis. The effect of acetazolamide on the Na/K ATPase activity was evaluated in an in vitro assay of primary CP epithelial cells isolated from rats. Acetazolamide significantly lowered ICP within 10 min of injection compared to the vehicle group (P < 0.05), reaching a maximum reduction at 55 min 66 ± 4% (P < 0.00001). Acetazolamide also significantly decreased the activity of the Na/K ATPase in CP epithelial cells compared to vehicle (P = 0.0022). Acetazolamide did not change the AQP1, AQP4 or Na/K ATPase mRNA content in the CP tissue. However, we did record an increase in the amount of AQP1 (p = 0.0152) and Na/K ATPase (p = 0.0411) protein in the membrane fraction of the CP, but not AQP4 (p = 0.0649). A single dose of acetazolamide lowers ICP and modulates the CSF secretion pathway in healthy rats – Firstly, by inhibiting the Na/K ATPase to slow the CSF production, secondly, by increasing AQP1 and Na/K ATPase protein in the membrane of the CP epithelial cells.